Clinical Application of Cone Beam Computed Tomography of the Rabbit Head: Part 2—Dental Disease - Riggs, G. G.; Cissell, Derek D.; Arzi, Boaz; Hatcher, David C.; Kass, Philip H.; Zhen, Amy; Verstraete, Frank J. M. (Frontiers in Veterinary Science, 2017)
Domestic rabbits are increasing in popularity as household pets; therefore veterinarians need to be familiar with the most common diseases afflicting rabbits including dental disease. Current diagnostic approaches include gross oral examination, endoscopic oral examination, skull radiography, and computed tomography (CT). Cone-beam CT (CBCT), a new oral and maxillofacial imaging modality that has the capability to produce high-resolution images, has not yet been described for use in evaluating dental disease in rabbits. A total of fifteen client-owned rabbits had CBCT, oral examination, dental charting, and dental treatment performed under general anesthesia. Images were evaluated using transverse and custom multi-planar (MPR), tridimensional (3D), and panoramic reconstructed images. The CBCT findings were grouped into abnormalities that could be detected on conscious oral examination vs. abnormalities that could not be detected by conscious oral examination. Potential associations between the two categories were examined by pairwise Fisher’s exact test with statistical significance determined by P<0.05. The most common findings identified on CBCT images were periodontal ligament space widening (14/15), premolar and molar malocclusion (13/15), apical elongation (13/15), coronal elongation (12/15), inflammatory tooth resorption (12/15), periapical lucency (11/15), moth-eaten pattern of osteolysis of the alveolar bone (9/15), ventral mandibular border contour changes (9/15), and missing teeth (8/15). Of the CBCT abnormalities likely to be observed on oral examination, coronal elongation (detectable on oral examination) was significantly associated with apical elongation (P=0.029). There were no other significant associations between CBCT findings that are also clinically detectable and CBCT findings that are not be detectable on oral examination. This suggests that pathology often exists that is not apparent upon oral examination. This study establishes the common CBCT findings associated with dental disease in rabbits and demonstrates the feasibility of this technology to diagnose and plan treatment in dental disorders in this species.